(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Catches of Psocoptera carried out in 1990-1991 by using a Taylor suction trap in an area of Po Valley are reported. In both years the first catches took piace in the middle of May, the last ones at the end of October. Twelve species were found. Six of these, precisely Lachesilla bernardi Badonnel, Ectopsocus vachoni Badonnel, Caecilius rhenanus (Tet.), Amphigerontia intermedia Tet., Oreopsocus montanus Kolbe, Philotarsus picicornis F., were recorded for the first time in Italy.